2022
DOI: 10.1155/2022/3595327
|View full text |Cite
|
Sign up to set email alerts
|

Channel Competition and Coordination of E-Commerce Platforms under Low-Carbon Environment: A Cooperative Game Approach

Abstract: The objective of “low-carbon supply chain” and the development of e-commerce platforms (as e-platform) has boosted the production and sales of low-carbon products. Although the e-platform’s involvement promotes the efficiency of low-carbon products circulation, it leads to channel competition and double marginalization. To mitigate these negative effects, in the context of low-carbon production, a three-player supply chain that contains a low-carbon manufacturer, an e-platform, and a retailer are investigated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…They found that both direct and agent selling may be optimal in the first stage, while in the second stage, agent sales are never optimal if the manufacturer and the retailer do not share additional market information. The development of e-commerce has also prompted many scholars to discuss the selection of distribution channels under the participation of e-commerce platforms, such as Wang et al [45], Liu et al [46], and Cao et al [47]. However, none of the above papers investigate the channel selection of green products.…”
Section: Channel Selection In Supply Chainmentioning
confidence: 99%
“…They found that both direct and agent selling may be optimal in the first stage, while in the second stage, agent sales are never optimal if the manufacturer and the retailer do not share additional market information. The development of e-commerce has also prompted many scholars to discuss the selection of distribution channels under the participation of e-commerce platforms, such as Wang et al [45], Liu et al [46], and Cao et al [47]. However, none of the above papers investigate the channel selection of green products.…”
Section: Channel Selection In Supply Chainmentioning
confidence: 99%